2010
DOI: 10.1111/j.1365-2745.2010.01697.x
|View full text |Cite
|
Sign up to set email alerts
|

Size‐dependent flowering and costs of reproduction affect population dynamics in a tuberous perennial woodland orchid

Abstract: Summary1. In woodland herbs, the probability of flowering and costs associated with reproduction may strongly depend on environmental context (shade vs. light habitats) and on plant size. This may be particularly true for tuberous orchids that inhabit woodlands, as the amount of incoming radiation and total leaf area strongly determine photosynthetic capacity and hence the amount of carbohydrates that can be relocated to below-ground storage organs that form next year's rosette and flowering stalk. 2. To fully… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
76
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 97 publications
(81 citation statements)
references
References 53 publications
3
76
1
1
Order By: Relevance
“…The asymptotic population growth rates (l) were 1.091 in the light habitat and 1.002 in the shade habitat, in agreement with previous results from these populations [40]. The predicted reproductive delay in the shade environment was driven entirely by the growth cost of flowering, as this was the only cost we detected and included in the IPM.…”
Section: Results (A) Parameter Estimation and Detection Of Reproductisupporting
confidence: 90%
“…The asymptotic population growth rates (l) were 1.091 in the light habitat and 1.002 in the shade habitat, in agreement with previous results from these populations [40]. The predicted reproductive delay in the shade environment was driven entirely by the growth cost of flowering, as this was the only cost we detected and included in the IPM.…”
Section: Results (A) Parameter Estimation and Detection Of Reproductisupporting
confidence: 90%
“…death (e-f) in two natural populations that were exposed to a grazing treatment and a control mowing treatment from 1999 to 2008. Data for both study populations are pooled per disturbance regime Such a relationship has previously been documented in several short-lived monocarpic species and some longlived polycarpic plants (see Bonser and Aarssen 2009;Weiner et al 2009;Jacquemyn et al 2010). However, flowering plants in grazed plots were significantly smaller than flowering plants in control plots, indicating that this grazing-mediated reduction in plant size was associated with a significant decrease in the vegetative size needed to realise investment in flowering.…”
Section: Discussionmentioning
confidence: 81%
“…Méndez and Karlsson (2004) documented differences in vegetative plant size at flowering among several Pinguicula vulgaris populations, which depended on the altitudes and soil moisture contents of these populations. In the woodland orchid Orchis purpurea, Jacquemyn et al (2010) also found significantly smaller threshold sizes for flowering in light environments. Although our data showed that P. veris was able to flower at significantly smaller sizes when herbivores were present, plants produced a significantly smaller number of flowers when they were grazed.…”
Section: Discussionmentioning
confidence: 82%
“…We attribute this result to the disparity of microclimate and light availability between habitats. Higher light availability can increase probability of flowering (Diez et al 2007;Jacquemyn et al 2010). Stable microclimatic conditions, e.g.…”
Section: Inter-annual Variability In Flowering In Different Habitatsmentioning
confidence: 99%